2013
DOI: 10.1175/jcli-d-12-00307.1
|View full text |Cite
|
Sign up to set email alerts
|

A Satellite Study of the Relationship between Sea Surface Temperature and Column Water Vapor over Tropical and Subtropical Oceans

Abstract: The known characteristics of the relationship between sea surface temperature (SST) and column water vapor (CWV) are reevaluated with recent satellite observations over tropical and subtropical oceans. Satellite data acquired by the Aqua Advanced Microwave Scanning Radiometer for Earth Observing System (AMSR-E), Atmospheric Infrared Sounder (AIRS)/Advanced Microwave Sounder Unit (AMSU) suite, the Tropical Rainfall Measuring Mission (TRMM) precipitation radar (PR), and the Quick Scatterometer (QuikSCAT) SeaWind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…To determine the typical boundary layer height, we adopt the water vapour scale height 15 (WSH; see Methods) as an index representing how deeply the near-surface atmosphere is mixed by thermal turbulent eddies. In Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the typical boundary layer height, we adopt the water vapour scale height 15 (WSH; see Methods) as an index representing how deeply the near-surface atmosphere is mixed by thermal turbulent eddies. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The scale height of water vapour WSH was derived as 15 .where q sfc is the water vapour mixing ratio at the surface and ρ d is the density of dry air (1.2 kg m −3 ) at the surface. For WSH, we used only 321 GPS stations within 20 km of the meteorological stations where observations of relative humidity and air pressure, required for calculating q sfc , are routinely performed with hourly interval (green circles in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…(A1a)-(A1c) of Large et al (1994). In this study, T a and q y,s are estimated from a logarithmic vertical profile within the simple surface layer (SL) model by Kanemaru and Masunaga (2013), u s 5 u ML 1 ln(z/z SL ) ln(z u /z SL ) [u( p s , T s ) 2 u ML ] and (8) q y,s 5 q y,ML 1 ln(z/z SL ) ln(z q /z SL ) [q y * (T s ) 2 q y,ML ],…”
Section: A Ocean Heat Budget Estimationmentioning
confidence: 99%
“…The AIRX data are interpolated from the neighboring eight grid pixels averaged together to fill data gaps due to clouds and rain. This interpolation decreases sampling bias, although the accuracy of satellite estimates is (Kanemaru and Masunaga 2013). We also use OLR derived by the AIRX product as a proxy of deep convection and QuikSCAT surface wind vector data.…”
Section: B Data Preprocessingmentioning
confidence: 99%
“…However, the increase of extreme rainfall does not necessarily follow the C-C scaling. Recent studies have found that temperature scaling rate for precipitation extremes can either be above or below the C-C scaling depending on various aspects including storm duration, climate region, temperature range, and the analysis method used (Hardwick Jones et al, 2010;Kanemaru and Masunaga, 2012;Lenderink and van Meijgaard, 2008;Panthou et al, 2014;Shaw et al, 2011;Westra et al, 2012).…”
Section: Introductionmentioning
confidence: 99%